A toolbox for the optimal design of run-of-river hydropower plants. (January 2019) - Yildiz, Veysel; Vrugt, Jasper A.
Abstract: Hydroelectric power is a relatively cheap, reliable, sustainable, and renewable source of energy that can be generated without toxic waste and considerably lower emissions of greenhouse gases than fossil fuel energy plants. Conventional hydroelectric plants produce energy by the controlled release of dammed reservoir water to one or more turbines via a penstock. The kinetic energy of the falling water produces a rotational motion of the turbine shaft and this mechanical energy is converted into electricity via a power generator. Dam-based plants are among the largest and most flexible power producing facilities in the world, yet their construction and operation is costly and can damage and disrupt upstream and downstream ecosystems and have catastrophic effects on downriver settlements and infrastructure. Run-of-the-river (RoR) hydroelectric stations are an attractive and environmentally friendly alternative to dam-based facilities. These plants divert water from a flowing river to a turbine and do not require the formation of a reservoir. Despite their minimal impact on the surrounding environment and communities, the potential of RoR plants has not been fully explored and exploited. For example, in the United States it is estimated that RoR plants could annually produce 60, 000 MW, or about 13% of the total electricity consumption in 2016. Here, we introduce a numerical model, called HYdroPowER or HYPER, which uses a daily time step to simulate the technical performance, energy production, maintenance and operational costs, and economic profit of a RoR plant in response to a suite of different design and construction variables and record of river flows. The model is coded in MATLAB and includes a built-in evolutionary algorithm that enables the user to maximize the RoR plant's power production or net economic profit by optimizing (among others) the penstock diameter, and the type (Kaplan, Francis, Pelton and Crossflow) design flow, and configuration (single/parallel) of the turbine system. Unlike other published models, this module of HYPER carefully considers each turbine's design flow, admissible suction head, specific and rotational speed in evaluating the technical performance, cost and economic profit of a RoR plant. Two case studies illustrate the power and practical applicability of HYPER. Some of their results confirm earlier literature findings, that (I) the optimum capacity and design flow of a RoR plant is controlled by the river's flow duration curve, (II) a highly variable turbine inflow compromises energy production, and (III) a side-by-side dual turbine system enhances considerably the range of workable flows, operational flexibility and energy production of a RoR plant. HYPER includes a GUI and is available upon request from the authors. Graphical abstract: High-level overview of HYPER with color coding for the different building blocks of the model. HYPER simulates the daily performance, investment, operation and maintenance costs, and economic profit of a RoR hydropower plant. Model inputs are highlighted in red. The design parameters (red diamond) play a key role in HYPER as they control the electricity production (gray), operational feasibility of the turbine system (green) and total costs (gray) of the RoR plant. A built-in optimization module (in blue) can be used to find optimal values of the design and/or project variables that maximize the net present value (NPV) of the plant. HYPER accommodates many other design objectives as well.Two different case studies are used to illustrate the power of HYPER. Our results demonstrate that HYPER readily defines the optimum size (design flow) and design of a RoR plant by maximizing the net difference between energy production and investment, operation and maintenance costs. The functional shape of the FDC determines in large part the optimum capacity and design of a RoR plant. A single turbine is unable to extract all the available power of the running water when confronted with highly variable streamflow conditions, whereas twoturbines in parallel increase the range of workable flows, and hence flexibility of operation and net profit of a RoR plant. The HYPER model includes a GUI and is available upon request from the authors. Image 1 Highlights: We present a numerical simulation model of a run-of-river (RoR) hydropower plant. This model, called HYPER, simulates the daily energy production, cost and economic profit of a RoR plant for a given flow duration curve and design variables. A built-in optimization module can estimate relevant decision variables such as turbine type (Pelton, Francis, Kaplan and Crossflow), configuration (serial/parallel) and design flow.